Serum Creatinine and Creatine Kinase as an Indicator for Gingival Wound Healing in Rabbits by Supplementation of Pomegranate Seed Extract - Rezan Majeed Omer (Diyala Journal of Medicine, 2021)
Background: Pomegranate (Punica granatum) is an edible fruit that has been described as a medical and therapeutic functional food in the Middle East and the Mediterranean.